Challenges of Social Reintegration for the 2013 Saudi Arabian Returnees in Ethiopia - Birara, Desalegn (International Journal of Humanities and Social Science Research, 2017)
Ethiopian nationals living in the Kingdom of Saudi Arabia (KSA) have been compelled to leave the country for causing an increase in the number of unemployed nationals of KSA. The crackdown was planned to create jobs for Saudi nationals by reducing the number of foreign workers. Due to the crackdown of illegal residents by the police, more than 140,000 Ethiopians returned home, as of December 22, 2013. Returnees were duly sent to their families as they arrived in Ethiopia by the provisions of IOM1 with overnight accommodation. However, reunification of returned migrants to their family and social environment has not been easy. Challenges of reintegration of the returnees to the main stream society vary across individuals. Emotional, health, psycho-social, and feelings of failure to meet family expectations take the lion’s share to determine the likelihood and extent of reintegration of returnees. Success to reintegrate depended on whether their migration experience abroad was successful, how they have integrated in the host society and what migration experience they have returned with. The challenges to reintegrate with local people came up with another migration; both intra-national and international. Returnees who did not appropriately reintegrated with the sociocultural environment are found vulnerable to substance abuse, alcoholism, and prostitution. Hopelessness, social isolation and development of low self-esteem prevail in the Saudi Arabian returnees. This study uncovered that reintegration of forced-returned migrants in their country of origin is a tough process. It is more likely to result in another migration and develop socially undesirable conducts.